Modul keagamaan untuk remaja hamil luar nikah di pusat perlindungan wanita di Selangor: Kajian pelaksanaan dan masalah / Nurul Husna Mansor - Nurul Husna , Mansor (2016)
“Religious Module for Unwed Pregnant Teenagers at Women‟s Shelter in Selangor: A Study on its Implementation and Problems.” This study outlines three objectives, where firstly it seeks to study the content of religious module for unwed pregnant teenagers at women‟s shelter in Selangor. Second, to analyze the approaches in religious modules implementation for unwed pregnant teenagers at women‟s shelter in Selangor. Third, to analyze the problems in the implementation of religious modules for unwed pregnant teenagers at women‟s shelter in Selangor. This qualitative case study applies multiple data collection methods which are interview, observation and documentation. A total of 17 informants were selected through purposive sampling technique from three women's shelters in Selangor. 6 informants were from Taman Seri Puteri Cheras, 7 informants from Baitul Ehsan and 4 informants from Darul Wardah. The data were then analyzed descriptively and thematically. The results of the study reveal that the content of the religious modules at women‟s shelters in Selangor are inclined towards the strengthening of belief through the six articles of faith, practicing religious worships of the five pillars of Islam and the formal and informal moral rehabilitation of the residents through verbal and non-verbal methods. Subsequently, the study has found that the six practical approaches as prescribed by Islam, namely good examples, gradual approach, establishing beneficial habits, admonition and guidance, observation and appropriate punishment and reward are practiced by women‟s shelters in Selangor through five varied platforms. Finally, the study has shown that there are seven issues in the implementation of religious modules which involve the residents, management of module, teaching staff, finance, parents and family of the residents, and community. Although the implementation of religious modules in women‟s shelters in Selangor is in line with Islamic recommendation, it is yet to be carried out fully. The implications of this research indirectly demonstrates that the quality of implementation for the existing religious modules at women‟s shelters in Selangor can still be improved in terms content, approaches and resolving the seven issue that have identified, based on the suggestions of this study.